Practical and Computational Studies of Bivalence Metal Complexes of Sulfaclozine and Biological Studies - Sharfalddin, Abeer A; Emwas, Abdul-Hamid; Jaremko, Mariusz; Hussien, Mostafa A. (Frontiers in Chemistry, 2021)
In the search for novel, metal-based drug complexes that may be of value as anticancer agents, five new transition metal complexes of sulfaclozine (SCZ) with Cu(II), Co(II), Ni(II), Zn(II), and Fe(II) were successfully synthesized. The chemical structure of each complex was characterized using elemental analysis (CHN), IR spectroscopy, UV–Vis spectroscopy, thermogravimetric analysis (TGA), and electronic paramagnetic resonance (EPR) spectroscopy. IR spectra indicated that the donor atoms were one sulfonyl oxygen atom and one pyrazine nitrogen atom, which associated with the metal ions to form a stable hexagonal coordination ring. The metal–ligand stability constant (Kf) revealed that Cu(II) and Ni(II) have good coordination stability among the metal compounds. Theoretical studies using DFT/B3LYP were performed to further validate the proposed structures. The obtained results indicated that Cu(II) has a trigonal bipyramidal geometry, whereas Fe(II), Co(II), and Ni(II) have an octahedral structure, while Zn(II) has a tetrahedral arrangement. The bio-activities of the characterized complexes were evaluated using DNA binding titration and molecular docking. The binding constant values for the metal complexes were promising, with a maximum value for the copper metal ion complex, which was 9 × 105 M-1. Molecular docking simulations were also carried out to evaluate the interaction strength and properties of the synthesized metal complexes with both DNA and selected cancer-relevant proteins. These results were supported by in vitro cytotoxicity assays showing that the Cu(II) and Ni(II) complexes display promising antitumor activity against colon and breast cancer cell lines.